PENGEMBANGAN MEDIA BUSY BOOK BERBASIS METODE GLOBAL PADA PEMBELAJARAN MEMBACA PERMULAAN - Yuliyati Irsa Lina; Rina Yuliana; Trian Pamungkas Alamsyah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This study aims to determine the steps to develop busy book learning media, the feasibility of busy book learning media products, and students' responses after using busy book learning media based on global methods in learning to begin with reading. This study use Sugiyono Rnd development model (2010:409) which has six steps in its development, namely: (1) Analysis of Problems, (2) Data Collection, (3) Product Design, (4) Design Validation, (5) Design Revision, (6) Product Testing. This research produces a product in the form of Busy Book as a learning media based on the assessment of material experts to get a percentage of 86.3% in the very feasible category, the assessment of linguists get a percentage of 85% in the very feasible category, the assessment of the media experts get a percentage of 90% in the very feasible category, and assessment in limited trials get a percentage of 94% with a very good category. Based on the results of the study it can be concluded that the Busy book media based on global methods can be said to be very feasible to use in learning to begin with after going through 6 stage.